Decoding the 'Bad Guy': Implementing the V.O.I.C.E. Framework in Analyzing Contemporary English Song Lyrics - Octa Pratama Putra; Zubairu Sani Abdulkadir; Sri Dewi Anggraini (Wanastra: Jurnal Bahasa dan Sastra, 2026)
The rapid evolution of contemporary popular music has transformed songs into complex multimodal texts that often pose challenges for traditional linguistic and literary analysis. This study introduces the V.O.I.C.E framework a simplified, analytical tool to decode the multi-layered meanings of Billie Eilish’s global hit, ‘Bad Guy’. Utilizing a qualitative descriptive method grounded in Multimodal Discourse Analysis (MDA), the research examines the song through five interconnected pillars: Vocal performance, production Originality, Identity construction, Cultural circulation, and Emotional resonance. The findings reveal that ‘Bad Guy’ achieves its subversive impact by deconstructing traditional pop tropes through ASMR-like whispered vocals, minimalist ‘bedroom’ production aesthetics, and the construction of an ‘anti-hero’ persona that challenges conventional gender roles. Furthermore, the study demonstrates that the V.O.I.C.E strategy effectively bridges the gap between complex semiotic theories and practical interpretation, providing a structured yet flexible roadmap for researchers and educators. Ultimately, this research highlights a shift toward ‘New Authenticity’ in English discourse, where sonic textures and digital cultural circulation are as significant as textual content in shaping contemporary identity and global resonance.